PERSEPSI WISATAWAN NUSANTARA TERHADAP DAYA TARIK WISATA EMBUNG KLEDUNG, TEMANGGUNG - Carrillo, Atanasius; Indrawati, Yayu; Oka Karini, Ni Made (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
The purpose of this research is to find out the perceptions of domestic tourists towards 4A (attraction, amenity, accessibility, ancillary) at Embung Kledung. This research is located in Embung Kledung, precisely on Jalan Raya Parakan - Wonosobo No. km. 12, Rice Field Area, Kledung, Kledung District, Temanggung Regency, Central Java, 56264. Data collection techniques used in this study included observation, distribution of questionnaires, interviews, literature study and documentation. The sampling technique in this study was purposive sampling by distributing questionnaires to domestic tourists who had visited the Embung Kledung tourist attraction. The number of respondents in this study were 100 people/respondents. The data analysis technique used in this study is a mixed methods analysis technique consisting of quantitative descriptive analysis and qualitative descriptive analysis. The results obtained from this study are the perceptions of domestic tourists towards attractions that have an average score of 3.35 and are in the very agree category. Domestic tourists' perception of amenities has an average score of 2.764 and is in the agree category. Domestic tourists' perception of accessibility has an average score of 2.543 and is in the agree category. Domestic tourists' perception of ancillary service has an average score of 2.746 and is in the agree category. However, there are several indicators that are in the category of strongly disagreeing, such as the variety of accommodations provided and the condition of the road leading to the Embung Kledung tourist attraction.